(untitled) (Bangladesh Journal of Neuroscience, 2017)
Occupational therapy is a branch of medicine which uses different methods to help physically and mentally ill people to develop, maintain, and recover skills needed to function in day to day life, as well as in workplace environments. Thus lives of millions of disabled all over the world are enhanced to a meaningful quality of life. Occupational therapists also focus much of their work on identifying and eliminating environmental barriers to independence and participation in daily activities. This is a client-centered practice that places emphasis on the progress towards the client’s goals. The interventions are made on adapting the environment, modifying the task, teaching the skill, and educating the client/family in order to increase participation in and performance of daily activities, particularly those that are meaningful to the client. They often find it challenging to implement client-centered and occupation-based assessment tools into practice. This part of rehabilitation medicine is neglected in our country. More work is needed to understand how best practices can be incorporated into a changing occupational therapy daily practice. The aim of this review article is to highlight the importance of occupational therapy and its application in improving the quality of life and quality adjusted life years in physically challenged persons. Bangladesh Journal of Neuroscience 2017; Vol. 33 (1): 34-38